Academic Achievement Deficits and Their Neuropsychological Correlates in Children Born Extremely Preterm. Issue 8 (October 2017) - Akshoomoff, Natacha; Joseph, Robert M.; Taylor, H. Gerry; Allred, Elizabeth N.; Heeren, Timothy; O'Shea, Thomas M.; Kuban, Karl C. K.
ABSTRACT: Objective: The purpose of this study was to examine the risks associated with learning disabilities (LDs) in a large sample of children born extremely preterm. We predicted higher than expected rates of LD, particularly in math, and children with LD in math, reading, or both would have lower intelligence quotients (IQs) and specific patterns of neuropsychological deficits. Methods: We evaluated academic achievement, rates of LD, and their neuropsychological correlates in the Extremely Low Gestational Age Newborns (ELGANs) Study cohort of 10-year-old children born at 23 to 27 weeks gestational age. Primary analyses focused on children without intellectual disability (verbal IQ > 70 and nonverbal IQ > 70; N = 668). Low achievement was defined as a standard score ⩽85 on the reading or math measures. Results: The risk of low math achievement scores (27%) was 1.5 times higher than the risk of low reading achievement scores (17%). Children were classified as having LD based on low achievement criteria in reading only (RD, 6.4% of sample), math only (MD, 16.2%), both reading and math (RD/MD, 8.3%), or no reading or math disabilities (No LD, 69.1%). Although all 3 LD groups had multiple neuropsychological weaknesses compared with the No LD group, the RD and MD groups had different patterns of neuropsychological impairment. Conclusion: These children from the ELGAN cohort had higher than expected rates of LD, particularly in mathematics, even after taking socioeconomic status into consideration. These results indicate specific cognitive weaknesses that differ between extremely preterm children with RD and MD. Abstract : This article has supplementary material on the web site: www.jdbp.org.